A systematic review of local vulnerability to climate change in developing country agriculture - Crane, Todd A.; Delaney, Aogán; Tamás, Peter A.; Chesterman, Sabrina; Ericksen, Polly J. (Wiley, 2017)
In the mid‐2000s, several highly‐cited papers called for improving conceptual coherence and methodological transparency in vulnerability research to support greater policy relevance. As reducing vulnerability rises on political agendas, identifying empirically validated measures will become increasingly important in the design and evaluation of multi‐site and multi‐scale programmatic interventions. Using a systematic review methodology, we analyze the current range of conceptual frameworks, operationalizations and research methodologies as used in empirical studies of local‐level vulnerability in agricultural settings. Detailed analysis of theories and methods provides a platform for moving toward reporting that supports valid comparisons between disparate studies. This in turn, enables the design and implementation of empirically‐informed programmatic interventions. The results show that earlier concerns remain relevant. Even the best reported cases do not support aggregated analysis because conceptual ambiguity and methodological heterogeneity renders each study effectively unique. While conceptualization is broadly consolidating around the IPCC framework, declaration of that framework does not predict consistent operationalization. Furthermore, emerging alternative frameworks, especially Vulnerability as Expected Poverty, reveal important limitations of the IPCC framework. Findings also highlight that reporting practices in vulnerability research perpetuate problematic ambiguity. When designing and reporting research, we recommend addressing six key questions that can help specify the objectives of the study: (1) Is this system vulnerable? (2) To what is this system vulnerable? (3) How vulnerable is this system? (4)What is causing this system to be vulnerable? (5) How is vulnerability distributed within the system? (6) What is causing the observed distribution of vulnerability within the system?